Development of Engineering Team Performance Management Applications in Apartments Using Extreme Programming Methods - Denny Jean Cross Sihombing (Universitas Islam Raden Rahmat, Malang, 2024)
This research aims to analyze and develop a performance management application for a team of technicians in an apartment using the Extreme Programming (XP) method. The initial phase involved in-depth data collection on the technician team's needs, challenges, and dynamics. Next, the application was developed with XP principles, providing features such as task tracking, job assignments, real-time status updates, and daily performance reporting. The final stage involved analyzing technology acceptance through internal trials and collecting feedback from the technician team and potential users. Technology acceptance simulations with data showed that the app successfully coped with operational scenarios and received positive feedback. The application was tested by users, with the number of users being 50% of the total number of users, with a user satisfaction rate of 85%. The conclusions of this study indicate that the engineering team successfully accepted the application, has the potential to improve performance management efficiency, and contributes to the understanding of the application of XP in application development for the property industry.